RVG-modified exosomes derived from mesenchymal stem cells rescue memory deficits by regulating inflammatory responses in a mouse model of Alzheimer’s disease - Cui, Guo-hong; Guo, Hai-dong; Li, Han; Zhai, Yu; Gong, Zhang-bin; Wu, Jing; Liu, Jian-sheng; Dong, You-rong; Hou, Shuang-xing; Liu, Jian-ren (Immunity & ageing, 2019)
Background Exosomes are lipid-bilayer enclosed nano-sized vesicles that transfer functional cellular proteins, mRNA and miRNAs. Mesenchymal stem cells (MSCs) derived exosomes have been demonstrated to prevent memory deficits in the animal model of Alzheimer’s disease (AD). However, the intravenously injected exosomes could be abundantly tracked in other organs except for the targeted regions in the brain. Here, we proposed the use of central nervous system-specific rabies viral glycoprotein (RVG) peptide to target intravenously-infused exosomes derived from MSCs (MSC-Exo) to the brain of transgenic APP/PS1 mice. MSC-Exo were conjugated with RVG through a DOPE-NHS linker. Results RVG-tagged MSC-Exo exhibited improved targeting to the cortex and hippocampus after being administered intravenously. Compared with the group administered MSC-Exo, in the group administered RVG-conjugated MSC-Exo (MSC-RVG-Exo) plaque deposition and Aβ levels were sharply decreased and activation of astrocytes was obviously reduced. The brain targeted exosomes derived from MSCs was better than unmodified exosomes to improve cognitive function in APP/PS1 mice according to Morris water maze test. Additionally, although MSC-Exo injected intravenously reduced the expression of pro-inflammatory mediators TNF-α, IL-β, and IL-6, but the changes of anti-inflammatory factors IL-10 and IL-13 were not obvious. However, administration of MSC-RVG-Exo significantly reduced the levels of TNF-α, IL-β, and IL-6 while significantly raised the levels of IL-10, IL-4 and IL-13. Conclusions Taken together, our results demonstrated a novel method for increasing delivery of exosomes for treatment of AD. By targeting exosomes to the cortex and hippocampus of AD mouse, there was a significant improvement in learning and memory capabilities with reduced plaque deposition and Aβ levels, and normalized levels of inflammatory cytokines.